Femicide in media - Mršević Zorica (Temida, 2014)
Media in Serbia explain femicide usually as caused by poverty and alcoholism. This style is gender blind and socially stereotyped because of neglected gender aspects of male violence against women. Particular problem is lack of problematizing obvious social “permission” of male violence. Femicide is regularly presented as an incident, allegedly impossible for anticipation rather than tragic epilogue of long lasting male violence against women which as such exists as a part of traditional gender social relations and roles. Media overlook that alcohol and poverty may only contribute to intensification of already existing, widely accepted domination of men and subordination of women. Media reports as a rule didn’t enter deeper into problems of institutional and social context in which is perpetrated long lasting violence as prefacing femicide. Media also never criticize the social behavior of neighbors, relatives and all others informed on the domestic violence, but rather avoid „mixing“into privacy matters. Thus violence escalates without barriers, eventually developed in femicide, murder a woman, victim of this, decades long lasting violence.